Pengaruh Pemberian Paket Pupuk terhadap Pertumbuhan dan Perubahan Sifat Kimia Tanah pada Tanaman Jeruk Keprok Tejakula - Trigunasih, Ni Made; Rai, I Nyoman; Wijaya, I Nyoman; Wijana, Gede; Wirya, Gusti Ngurah Alit Susanta; Widhianthini, Widhianthini; Mayadewi, Ni Nyoman Ari; Yudha, I Kadek Wisma; Utama, I Wayan Eka Karya; Wigunanda, I Wayan Surya Aditya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2025)
Purpose: This research aims to analyze the effect of organic and inorganic fertilizer packages on the growth of Tejakula tangerine plants and changes in soil chemical properties after being given organic and inorganic fertilizer packages. Research methods: The method used in this research was a Randomized Block Design (RAK) with 1 (one) factor. The treatment tested was the fertilizer package dose (P), consisting of 3 levels, namely organic fertilizer/cow manure (Po), organic cow manure + 22.6 g Urea fertilizer + 4 g KCl fertilizer + Phonska Plus 15 fertilizer -15-15 dose 84 g (Ph), and organic cow manure fertilizer + Urea fertilizer dose 22.6 g, KCl fertilizer dose 4 g, Phonska Plus fertilizer 15-15-15 dose 84 g + mycorrhizal biofertilizer + liquid organic fertilizer (POC) probiotics (Pc). Each treatment was repeated 8 times to obtain 24 treatments. Findings: The response to the fertilizer package had a significant to very significant effect on plant growth, such as increasing plant height, increasing the number of primary branches, increasing stem diameter and number of leaves. The fertilizer package that gave the highest response to plant height, number of leaves, while the increase in stem diameter had the same effect. Primary branch augmentation is the most influential Ph package but is not significantly different from PC. The effect of fertilizer packages on changes in soil chemical properties is that pH is neutral, DHL is classified as low to very high, C-org is classified as high, N-tot is classified as medium, P-available and K-available is classified as very high. Implication: The effect of mixed organic, inorganic and biological fertilizers and probiotic POC provide the best response to plant growth and increase DHL in the soil.